Digital divide, economic growth and potential poverty reduction : the case of the English Speaking Caribbean - Henry, Lester (2004)
Seeks to ascertain how the adoption of computer and internet technology can enhance the growth prospects for Caribbean countries, and thereby have a significant impact on the reduction of poverty in the region.